O Šokcima u mađarskim enciklopedijskim izdanjima - BLAŽETIN, STJEPAN (SlavVaria, 2021)
About the inclusions of the „Šokac” ethnic group in Hungarian encyclopaedic texts. This work does not intend to answer who the „Šokac” ethnic group are, but rather to introduce the ways in which Hungarian encyclopaedic texts represent the „Šokac” people and outline what is emphasised in certain entries or texts that refer to them. The work scrutinises some of the most significant encyclopaedic volumes issued in the period between the years of the late-nineteenth century and the first decade of the twenty-first century. Such volumes are most often intended for the widest possible audience of readers, and therefore mirror the ideological background of their authors, editors, publishers and possibly the reigning authority of their time. In other words, these volumes serve as the reflection of the era they were created in. At the same time, they compile various aspects of scientific and scholarly research and its results, pertaining to the specific historical era of when they were issued.